A high‐fat diet exacerbates the Alzheimer's disease pathology in the hippocampus of the AppNL−F/NL−F knock‐in mouse model. Issue 8 (10th July 2021) - Mazzei, Guianfranco; Ikegami, Ryohei; Abolhassani, Nona; Haruyama, Naoki; Sakumi, Kunihiko; Saito, Takashi; Saido, Takaomi C.; Nakabeppu, Yusaku
Abstract: Insulin resistance and diabetes mellitus are major risk factors for Alzheimer's disease (AD), and studies with transgenic mouse models of AD have provided supportive evidence with some controversies. To overcome potential artifacts derived from transgenes, we used a knock‐in mouse model, App NL−F/NL−F, which accumulates Aβ plaques from 6 months of age and shows mild cognitive impairment at 18 months of age, without the overproduction of APP. In the present study, 6‐month‐old male App NL−F/NL−F and wild‐type mice were fed a regular or high‐fat diet (HFD) for 12 months. HFD treatment caused obesity and impaired glucose tolerance (i.e., T2DM conditions) in both wild‐type and App NL−F/NL−F mice, but only the latter animals exhibited an impaired cognitive function accompanied by marked increases in both Aβ deposition and microgliosis as well as insulin resistance in the hippocampus. Furthermore, HFD‐fed App NL−F/NL−F mice exhibited a significant decrease in volume of the granule cell layer in the dentate gyrus and an increased accumulation of 8‐oxoguanine, an oxidized guanine base, in the nuclei of granule cells. Gene expression profiling by microarrays revealed that the populations of the cell types in hippocampus were not significantly different between the two mouse lines, regardless of the diet. In addition, HFD treatment decreased the expression of the Aβ binding protein transthyretin (TTR) in App NL−F/NL−F mice, suggesting that the depletion of TTR underlies the increased Aβ deposition in the hippocampus of HFD‐fed App NL−F/NL−F mice. Abstract : Insulin resistance and diabetes mellitus are major risk factors for Alzheimer's disease (AD). In this paper, we showed that type 2 diabetic conditions induced by chronic high‐fat diet treatment exacerbated pre‐existing AD pathology such as Aβ deposition, microgliosis, and oxidative DNA damage in a knock‐in mouse model of AD, App NL‐F/NL‐F . This was accompanied by decreased expression of transthyretin, a protein that can bind to the Aβ peptide, suppress its aggregation, and promote its clearance.